Salt Promotes Inflammation: Mechanistic Insights - Editorial Office ROS (Reactive Oxygen Species, 2022)
It has been well established that high dietary salt intake promotes inflammation and contributes to the pathogenesis of many inflammatory disorders, especially cardiovascular diseases. Several recent studies published in prestigious journals have further elucidated the molecular pathways underlying high salt-induced inflammation, including identification of the involvement of mitochondrial electron transport chain and the Nrf2-SIRT3 signaling axis. These novel findings provide important mechanistic insights and offer potential opportunities for developing modalities for intervention of high salt-associated pathophysiological conditions. (First online: March 1, 2022) REFERENCES Thornton SN. Sodium intake, cardiovascular disease, and physiology. Nat Rev Cardiol 2018; 15(8):497. doi: https://dx.doi.org/10.1038/s41569-018-0047-3 Cook NR, He FJ, MacGregor GA, Graudal N. Sodium and health-concordance and controversy. BMJ 2020; 369:m2440. doi: https://dx.doi.org/10.1136/bmj.m2440 Wu C, Yosef N, Thalhamer T, Zhu C, Xiao S, Kishi Y, et al. Induction of pathogenic TH17 cells by inducible salt-sensing kinase SGK1. Nature 2013; 496(7446):513–7. doi: https://dx.doi.org/10.1038/nature11984 Wilck N, Matus MG, Kearney SM, Olesen SW, Forslund K, Bartolomaeus H, et al. Salt-responsive gut commensal modulates TH17 axis and disease. Nature 2017; 551(7682):585–9. doi: https://dx.doi.org/10.1038/nature24628 Zhang WC, Zheng XJ, Du LJ, Sun JY, Shen ZX, Shi C, et al. High salt primes a specific activation state of macrophages, M(Na). Cell Res 2015; 25(8):893–910. doi: https://dx.doi.org/10.1038/cr.2015.87 Geisberger S, Bartolomaeus H, Neubert P, Willebrand R, Zasada C, Bartolomaeus T, et al. Salt Transiently inhibits mitochondrial energetics in mononuclear phagocytes. Circulation 2021; 144(2):144–58. doi: https://dx.doi.org/10.1161/CIRCULATIONAHA.120.052788 Ros EO. Sodium ion regulates mitochondrial ROS. React Oxyg Species (Apex) 2021; 11:n5–n6. doi: https://dx.doi.org/10.20455/ros.2021.n.805. Shadel GS, Horvath TL. Mitochondrial ROS signaling in organismal homeostasis. Cell 2015; 163(3):560–9. doi: https://dx.doi.org/10.1016/j.cell.2015.10.001 Lanaspa MA, Kuwabara M, Andres-Hernando A, Li N, Cicerchi C, Jensen T, et al. High salt intake causes leptin resistance and obesity in mice by stimulating endogenous fructose production and metabolism. Proc Natl Acad Sci USA 2018; 115(12):3138–43. doi: https://dx.doi.org/10.1073/pnas.1713837115 Gao P, You M, Li L, Zhang Q, Fang X, Wei X, et al. Salt-Induced hepatic inflammatory memory contributes to cardiovascular damage through epigenetic modulation of SIRT3. Circulation 2022; 145(5):375–91. doi: https://dx.doi.org/10.1161/CIRCULATIONAHA.121.055600 Dikalova AE, Pandey A, Xiao L, Arslanbaeva L, Sidorova T, Lopez MG, et al. Mitochondrial deacetylase Sirt3 reduces vascular dysfunction and hypertension while Sirt3 depletion in essential hypertension is linked to vascular inflammation and oxidative stress. Circ Res 2020; 126(4):439–52. doi: https://dx.doi.org/10.1161/CIRCRESAHA.119.315767 Kim A, Koo JH, Lee JM, Joo MS, Kim TH, Kim H, et al. NRF2-mediated SIRT3 induction protects hepatocytes from ER stress-induced liver injury. FASEB J 2022; 36(3):e22170. doi: https://dx.doi.org/10.1096/fj.202101470R